Amphiphilic tetra-PCL-b-PEG star block copolymers using benzoxazinone-based linking groups. Issue 16 (3rd April 2023) - Bunk, Carolin; Komber, Hartmut; Lang, Michael; Fribiczer, Nora; Geisler, Martin; Formanek, Petr; Jakisch, Lothar; Seiffert, Sebastian; Voit, Brigitte; Böhme, Frank
Abstract : Two well-defined amphiphilic tetra-arm star block copolymers with a poly(ε-caprolactone) core and poly(ethylene glycol) arms were prepared by a hetero-complementary linkage reaction and studied with respect to their solution behavior in water. Abstract : In this study, two well-defined amphiphilic tetra-arm star block copolymers with a poly(ε-caprolactone) (ε-CL) core and poly(ethylene glycol) (PEG) arms with different length (800 g mol −1 and 2100 g mol −1 ) were prepared by a hetero-complementary linking reaction and studied in detail. A pentaerythritol core was used as an initiator for the ring-opening polymerization (ROP) of ε-CL, generating a hydroxy-terminated tetra-arm star polymer (tetra-PCL–OH) with controlled molar mass ( M n ∼ 10 kg mol −1 ) and low dispersity ( Đ < 1.1). After end group esterfication with 2-(4-nitrophenyl)-4-oxo-4 H -benzo[ d ][1, 3]oxazine-7-carboxylic acid chloride, linear hydrophilic PEG was attached to the respective tetra-PCL to obtain tetra-PCL- b -PEG star block copolymers. The behavior of the two amphiphilic block copolymers was studied in water by a combination of variable-temperature 1 H NMR spectroscopy, DLS, DSC and TEM measurements. In the case of longer PEG arms, spherical micelles form at elevated temperatures and remain stable at room temperature over days. Transmission electron microscopy indicates a possible slow morphology change of spherical micelles into long cylindrical micelles after one week. Suspensions of the star block copolymers with the short PEG arms in water remain cloudy, in contrast to the star block copolymers with long arms.